PERLINDUNGAN HUKUM TERHADAP KONSUMEN E-COMMERCE DALAM HAL KETIDAKSESUAIAN PRODUK PADA WEBSITE - Bisma Putra Pratama; Susanti Sembiring (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Today's technology and information makes it easier for consumers to make transactions and buy the desired goods just by looking at e-commerce websites. The use of information systems and transactions today is also accompanied by a negative impact on consumers where the goods received do not match the reality that is on the catalog on the internet, this is not in accordance with Law Number 8 of 1999 concerning Consumer Protection, this raises many questions related to responsibility business actors and legal protection for consumers regarding losses in purchasing goods in e-commerce transactions that are not in accordance with the provider's website, there is a gap in the position of consumers and business actors which results in harm to consumers. Based on the background of the problems above, the formulation of the problem in this study includes, How is legal protection for consumers in online buying and selling agreements via the internet (E-Commerce) in Indonesia and Legal remedies taken by consumers if they experience losses. This type of research is library research, meaning a study by reviewing books related to this research that come from libraries or the Internet. The research method used in writing this research is library research which is normative juridical. Normative juridical means statutory regulations and norms that apply in society or also those concerning customs that apply in society. In legal research, there is an approach, namely the approach, namely the statutory approach and the conceptual approach. With this approach, researchers will get information from various aspects regarding the issue being tried to find an answer. it's a loss. The results of this discussion found that legal protection for consumers who use e-commerce transactions in the event of a loss is regulated in the provisions of the Civil Code, Law Number 8 of 1999, and Law Number 11 of 2008. However, the regulations in Indonesia has not been able to specifically accommodate legal protection for consumers who use e-commerce transactions, so it is hoped that the Law on Consumer Protection and the Electronic Transaction Information Law will accommodate more legal protection for consumers who use e-commerce transactions. In Indonesia, there are two legal remedies that consumers can take if they suffer losses in online trading transactions, namely by court or out of court (consultation, negotiation, mediation, or expert judgment) according to the agreement of each party.Keywords: Consumer Protection, E-Commerce, Product.